Diffusivities in Binary Mixtures of Ammonia Dissolved in n-Hexane, 1-Hexanol, or Cyclohexane Determined by Dynamic Light Scattering and Molecular Dynamics Simulations - Piszko, Maximilian; Lenahan, Frances; Steinacker, Sarah-Lena; Klein, Tobias; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2023)
Binary mixtures of ammonia (NH3) dissolved in cyclohexane, n-hexane, or 1-hexanol are investigated by dynamic light scattering, polarization-difference Raman spectroscopy (PDRS), and equilibrium molecular dynamics (EMD) simulations. Investigations are performed in macroscopic thermodynamic equilibrium at or close to saturation conditions up to pressures p of 3 MPa and at temperatures T between 303 and 423 K. Besides studying the influence of a polar gas dissolved in a liquid on the Fick or mutual diffusion coefficient D11, the applicability of EMD simulations to systems consisting of polar/polar or nonpolar/polar solvent/solute combinations is also evaluated. At small compositions of NH3, D11 in mixtures with cyclohexane or 1-hexanol shows the expected Arrhenius-like increase with increasing T. For mixtures of n-hexane and NH3, a departure from the expected increase with T is observed at low T, which is related to a strong clustering of the NH3 molecules, leading to a slowing down of D11. This behavior can be related to the weak interactions between polar NH3 and nonpolar n-hexane. In comparison, much stronger interactions are observable between polar NH3 and polar 1-hexanol. The composition-dependent trend of D11 in mixtures of n-hexane or 1-hexanol with NH3 is also investigated. Here, D11 increases with increasing amount of dissolved NH3 in mixtures of 1-hexanol + NH3 for all investigated T. For n-hexane + NH3, at the lowest T, D11 is first constant and increases afterwards with increasing amount of dissolved NH3. At larger T, D11 is first constant and slightly decreases afterwards. Due to a lack of solubility data, the composition of the investigated mixtures could not be determined by PDRS. Yet, the composition-dependent intensity ratios between contributions related to NH3 and the respective solvent obtained from PDRS are reported. This allows the determination of composition, once reliable solubility data are available.
CRIS-Team Scopus Importer:2023-12-01